Reseña de Muñoz Núñez, M. D. (1999), El Análisis Funcional del Significado, Cádiz, Universidad de Cádiz. - Rodríguez-Piñero Alcalá, Ana Isabel (Pragmalingüística, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]--> Se trata de reseña de Muñoz Núñez, M. D. (1999), El Análisis Funcional del Significado, Cádiz, Universidad de Cádiz.